Algorithmic Creativity and Copyright: Can AI Be the Author of a Work? - Ruiz Osuna, Pablo; Carbajal, Isaac; Vanioff, Ivan; Pauketat, Janet V.T. (Ius Humani. Jornal do direito, 2026)
The development of artificial intelligence systems capable of generating texts, images, music, code, and other formally original creations has reopened the debate on the classical foundations of copyright law. This article examines whether an artificial intelligence system can be considered the author of a work and what the legal, ethical, and philosophical implications are of either accepting or rejecting that possibility. To this end, it analyses the concept of algorithmic creativity, the traditional notion of authorship based on human intervention, and the main criteria used by copyright law to recognize the originality of a work. It also explores the problems raised by AI-generated works in relation to ownership, liability, moral and economic rights, and the protection of the interests of programmers, users, companies, and autonomous systems. This article further argues that, in view of the development of increasingly complex and autonomous machines, it is necessary to recognize that such systems are creating creative works that may be as original as, or even more original than, human works. This calls for a shift in perspective leading to legislative reform capable of recognizing the “co-creation” of works through human-machine interaction, both in law and in society.